Patterns and trends of child and maternal nutrition inequalities in Nigeria - Omilola, Babatunde (International Food Policy Research Institute, 2010)
Despite the fact that nonincome dimensions of well-being such as nutrition and health are now placed on the global development agenda, substantial gaps remain in our knowledge about patterns and trends in nutrition inequalities in many developing countries. The main objective of this paper is to document a useful starting point for understanding the determinants of inequalities in nutritional status and provide some understanding of the proximate causes of inequalities in nutritional status as well as the factors responsible for inequalities in health and nutritional status of children and women in the policy debate. Using Nigeria as a case study and using data from the Nigerian Demographic and Health Survey, this paper measures and decomposes the patterns and trends of inequalities in child and maternal nutritional status in Nigeria. In particular, the paper decomposes observed nutritional inequalities into inequalities between and within demographic and socioeconomic groups to ascertain the relative contributions of the between-groups and within-group components of inequalities. To identify the most vulnerable groups in Nigeria, the paper also explores the prevalence of child and maternal malnutrition in Nigeria. The paper finds that within-group inequalities are the sources of most inequalities in the nutritional status of children and women in Nigeria. Inequalities between demographic and socioeconomic groups are less important. Child and maternal malnutrition are concentrated among the least educated households, the rural population, the north (in particular its Hausa ethnic group), and those who drink water from public wells. Malnutrition in Nigeria is a vicious cycle in that child malnutrition can be partly traced back to low birth weight (and therefore to maternal malnutrition). To interrupt this vicious cycle, the Nigerian government should take targeted and concerted actions that focus attention on addressing within-group inequalities. Intervention in the areas of primary healthcare, home-based caring practices, access to basic services (such as safe drinking water and good sanitation), education of women, and direct nutritional interventions for malnourished children seem the most appropriate.